Avaliação de impacto da capacitação no departamento de oftalmologia e ciências visuais da UNIFESP: um estudo de caso - Santos, Maria Jose Conceição dos [UNIFESP] (2016)
The aim of this study was to investigate and map the impact of training activities and training with the needs raised by the Federal University of São Paulo. The research method was focused on investigating the perception of the servers on the offered courses. In this sense the case study, it was through applying descriptive questionnaire, quantitative, semi-structured with 22 closed multiple choice questions, applied to the population and sample of 20 servers, of both sexes and all education levels, classes D and E and various functions that make up the framework of the Career Plan of Positions Technical and administrative Education, crowded in the Academic Department of Ophthalmology and Visual Sciences at UNIFESP. Method - The research instrument was limited to a population survey study, servers who performed or were conducting training and / or training courses in the period 2012-2015 or nearing completion. The survey was conducted in the workplace, in the period 12-24 March 2016. The results were based on analysis of the survey responses, extracted documentary research site and page of the University, Dean of Personnel Management, Department of Development and Personnel Management, Training Committee, Campus Training Subcommittee São Paulo and Supervision Internal Commission of Career Plan of Positions Technical and administrative Education - UNIFESP. Most respondents in this class and, higher level of formal education in the institution over 20 years and female, have over the training requirement of the position in the institution. The degree of satisfaction with the effectiveness of the Training Program and Impact of Training Action, observed the responses of technicians and managers that the program does not meet or meets very little to individual and institutional needs. Conclusion - It was observed in this case study, after analysis, the training program sometimes meets the individual and institutional needs, perhaps for lack of an assessment tool impact of actions taken. The perception of the servers as the courses offered at the institution is dissatisfaction and demotivation, understanding that although more than ten of the conquest of Career Plan - PCCTAE, little has evolved as the management strategies to address the dysfunctions of training. You can see that the development is not in line with the National Plan for Professional Development (PNDP), Institutional Development Plan (IDP), Development Plan members Career (CIDP) and Multi-Year Plan (PPA).